The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ph13020031
|View full text |Cite
|
Sign up to set email alerts
|

Cell Secretome: Basic Insights and Therapeutic Opportunities for CNS Disorders

Abstract: Transplantation of stem cells, in particular mesenchymal stem cells (MSCs), stands as a promising therapy for trauma, stroke or neurodegenerative conditions such as spinal cord or traumatic brain injuries (SCI or TBI), ischemic stroke (IS), or Parkinson’s disease (PD). Over the last few years, cell transplantation-based approaches have started to focus on the use of cell byproducts, with a strong emphasis on cell secretome. Having this in mind, the present review discusses the current state of the art of secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 150 publications
(167 reference statements)
1
45
0
Order By: Relevance
“…Then, culture media were removed, and the cells incubated for 24 h with an equivalent volume of the secretome derived from untreated astrocytes and from pre-miR-146a and VS treated cells. Secretome contains soluble factors and vesicular fractions as sEVs, essentially containing miRNAs (Pinho et al, 2020). We showed that sEVs were preferentially collected by microglia than by MNs, when in coculture (Pinto et al, 2017).…”
Section: N9-microglia Cell Culture and Treatment With Astrocyte-derived Secretome And Sevsmentioning
confidence: 80%
“…Then, culture media were removed, and the cells incubated for 24 h with an equivalent volume of the secretome derived from untreated astrocytes and from pre-miR-146a and VS treated cells. Secretome contains soluble factors and vesicular fractions as sEVs, essentially containing miRNAs (Pinho et al, 2020). We showed that sEVs were preferentially collected by microglia than by MNs, when in coculture (Pinto et al, 2017).…”
Section: N9-microglia Cell Culture and Treatment With Astrocyte-derived Secretome And Sevsmentioning
confidence: 80%
“…Although the mechanism of MSCs’ action has not been completely understood, numerous studies have demonstrated the extracellular secreted factors and vesicles—their secretome as their “active ingredients” for regenerative and cytoprotective effects, and immunomodulatory property of the MSC-based therapy [ 57 , 58 ]. MSC-derived soluble factors and vehicle-bound substances (secretome or conditional medium) from different sources consist of IFN-γ, IL-17, IL-10, IL-6, TGF-β, IL-2, TNF-α, and HLA (for immunomodulation), and GDNF, FGF, IGF, BDNF, PEGF, PDGF, miRNAs, VEGF, and MMPs (for cell survival/growth and tissue remodeling) [ 59 61 ]. The composition of the secretome of MSCs appears to vary significantly, depending on the age of the host and niches where the cells are collected [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are pluripotent, non-hematopoietic stem cells with the ability to differentiate into a diverse number of cell lineages, including chondrocytes, osteoblasts, and neuron-like cells ( Uccelli et al, 2006 ; Williams and Keating, 2008 ). They can be isolated from almost all tissues in mammals including bone marrow (BM), adipose tissue or other tissues ( Pinho et al, 2020 ) and are easy to culture and effectively expand. BM-MSCs are the most common, while in recent years adipose-derived MSCs have become increasingly popular due to their easy availability and high yield ( Faghih et al, 2017 ; Perteghella et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%